KELAYAKAN LIMBAH KALENG SUSU SEBAGAI BAHAN DASAR PEMBUATAN AKSESORIS PENGANTIN PADANG (Beauty and Beauty Health Education, 2021)
Abstract. The need for cans continues to increase along with technological developments. Milk cans are waste for the Petarukan environment which causes problems due to the rapid growth of shops selling milk-based drinks, causing a buildup of milk cans in the Petarukan market. In the community, milk cans are collected and brought to the collectors to be exchanged for money. In addition, based on interviews, the waste milk cans are used as pencil cases, piggy banks, flower vases, etc. Based on the description above, no one has used milk cans as accessories, Padang bridal accessories generally use gold or brass as basic materials. So the researcher wants to use milk cans waste as Padang bridal accessories, because milk cans have good texture characteristics and have strong resistance. The research objectives (1) are to determine the product validity of milk cans waste for Padang bridal accessories. (2) to determine the feasibility of the product based on the preference test. This study uses quantitative research methods with experiments. The object of research is Padang bridal accessories. The research subjects consisted of 3 expert judgment and 15 moderately trained panelists. Product validity used 3 expert panelists, preference test using 15 beauty salons as moderately trained panelists. Data collection techniques using observation and documentation. Data analysis using descriptive percentage. The types of Padang bridal accessories made from milk cans are galang ula, galang bapahek, earrings, panyiraman necklaces, gadang necklaces, laca, serapak bananas, kote-kote and suntiang. The results of the descriptive analysis showed that the Padang bridal accessories product was declared very valid by 3 experts. From the validity of the product, it showed that the whole product was declared valid with an average value of 90% with the highest score of 100% for P4 products and the lowest score of 87% for P1 products. and P2. The results of the nine product preference test got the highest score of 97.5%, namely for the criteria for product P3, product P4 and product P6, for the lowest score for product P1 and product P5, namely 87%. Suggestions for expert beauticians to be more creative and innovative in utilizing surrounding materials. Keywords: Waste, Milk cans, Padang bridal accessories Abstrak. Kebutuhan kaleng terus mengalami peningkatan seiring dengan perkembangan teknologi. Kaleng susu merupakan limbah bagi lingkungan Petarukan yang menyebabkan masalah diakibatkan pesatnya kedai yang menjual minuman dari bahan dasar susu, sehingga menyebabkan penumpukan kaleng susu dipasar Petarukan. Dimasyarakat kaleng susu dikumpulkan dan dibawa kepengepul untuk ditukar dengan uang, selain itu berdasarkan hasil wawancara limbah kaleng susu dimanfaatkan untuk menjadi tempat pensil, celengan, vas bunga dll. Berdasarkan uraian diatas belum ada yang memanfaatkan limbah kaleng susu sebagai aksesoris, aksesoris pengantin Padang pada umumnya menggunakan bahan dasar emas atau kuningan. Maka peneliti ingin memanfaatkan limbah kaleng susu sebagai aksesoris pengantin Padang, karena kaleng susu memiliki karakteristik teksture yang bagus dan memiliki ketahan yang kuat.Tujuan penelitian (1) untuk mengetahui validitas produk dari limbah kaleng susu untuk aksesoris pengantin Padang. (2) untuk mengetahui Kelayakan produk berdasarkan uji kesukaan. Penelitian ini menggunakan metode penelitian kuantitatif dengan ekperimen. Objek penelitian adalah aksesoris pengantin Padang. Subjek penelitian yaitu terdiri dari 3 exper judgment dan 15 panelis agak terlatih Validitas produk menggunakan 3 panelis ahli, uji kesukaan menggunakan 15 salon kecantikan sebagai panelis agak terlatih.Teknik pengumpulan data menggunakan observasi dan dokumentasi. Analisis data menggunakan desktiptif presentase. Jenis aksesoris pengantin Padang yang dibuat dari limbah kaleng susu yaitu galang ula, galang bapahek, anting, kalung panyiraman, kalung gadang, laca, pisang serapak, kote-kote dan suntiang. Hasil analisis deskriptif menunjukan bahwa produk aksesoris pengantin Padang dinyatakan sangat valid oleh 3 exper jugment dari validitas produk menunjukan bahwa keseluruhan produk dinyatakan valid dengan rata-rata nilai 90,00% dengan skor tertinggi 100% untuk produk P4 dan skor terendah 87% untuk produk P1 dan P2. Hasil uji kesukaan produk sembilan mendapatkan skor tertinggi 97,5% yaitu untuk kriteria produk P3, produk P4 dan produk P6, untuk skor terendah produk P1 dan produk P5 yaitu 87%. Saran untuk ahli praktisi kecantikan untuk lebih kreatif dan inovatif dalam memanfaatkan bahan sekitar. Kata Kunci: Limbah, Kaleng susu, Aksesoris pengantin Padang